2017
DOI: 10.1248/bpb.b16-00577
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Green Propolis Promotes Weight Loss and Reduces Fat Accumulation in C57BL/6 Mice Fed A High-Fat Diet

Abstract: Propolis is a bee product with various biological properties. C57BL/6 mice were fed a high-fat diet and treated with propolis for 14 weeks. Body weight in mice treated with 2% propolis was less than that in control mice from 3 weeks after the start of treatment until 14 weeks except for the 7th week. Mice treated with propolis showed significantly lower epididymal fat weight and subcutaneous fat weight. Infiltration of epididymal fat by macrophages and T cells was reduced in the propolis group. Supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…No modification of energy expenditure was observed under propolis supplementation, but an increase of fecal lipids was observed, suggesting that Brazilian propolis reduced intestinal fat absorption. [13] The molecular mechanism(s) underlying the effect of propolis on weight gain limitation remains elusive. B) 3T3-L1 adipocytes were incubated with growing concentrations of PPEE for 24 h. Expression of Nrf2-target genes coding for antioxidant enzymes measured through qPCR and expressed relative to 18S ribosomal RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No modification of energy expenditure was observed under propolis supplementation, but an increase of fecal lipids was observed, suggesting that Brazilian propolis reduced intestinal fat absorption. [13] The molecular mechanism(s) underlying the effect of propolis on weight gain limitation remains elusive. B) 3T3-L1 adipocytes were incubated with growing concentrations of PPEE for 24 h. Expression of Nrf2-target genes coding for antioxidant enzymes measured through qPCR and expressed relative to 18S ribosomal RNA.…”
Section: Discussionmentioning
confidence: 99%
“…No modification of energy expenditure was observed under propolis supplementation, but an increase of fecal lipids was observed, suggesting that Brazilian propolis reduced intestinal fat absorption. [ 13 ] The molecular mechanism(s) underlying the effect of propolis on weight gain limitation remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several reports have demonstrated that Brazilian green propolis extracts have hypoglycemic effects [26,27], there are no reports on the influence of treatment with baccharin alone in vivo. In the present animal study, we investigated the effects of baccharin on glucose metabolism and insulin sensitivity in obese diabetic ob/ob mice.…”
Section: Discussionmentioning
confidence: 99%
“…The authors presumed this effect was due to a reduction of fat absorption by propolis because they observed increased excretion of fat into the feces. 82 Not all studies have used Brazilian green propolis. One study showed that administration of an ethanol extract of Croatian propolis (50 mg/kg) for 30 days significantly attenuated weight gain in a mouse model of diet-induced obesity.…”
Section: Antiobesity and Antidiabetes Effects Of Propolismentioning
confidence: 99%